Correlations of GDF-15 with sST2, MMPs, and worsening functional capacity in idiopathic dilated cardiomyopathy: Can we gain new insights into the pathophysiology?. (18th January 2018) - Nair, Nandini; Gongora, Enrique
Growth and differentiation factor-15 (GDF-15) has been implicated in fibrosis, inflammation, and ventricular remodeling. The role of GDF-15 in the regulation of cardiac remodeling in idiopathic dilated cardiomyopathy (DCM) remains poorly defined. This study attempts to analyze the molecular interactions between GDF-15 and markers of fibrosis as well as its positive correlations with worsening functional capacity. The study population consisted of 24 DCM patients and 8 control subjects. All DCM patients had normal coronary angiographic studies. Plasma levels of GDF-15, matrix metalloproteinase-2 (MMP2), MMP3, MMP9, tissue inhibitor of MMP 1 (TIMP1), and soluble suppression of tumorigenicity-2 protein (sST2) were determined by enzyme-linked immunosorbent assays. Brain Natriuretic Peptide (BNP) was measured as per core laboratory protocol assay at Scott and White Memorial Hospital core laboratory. Correlation analysis was performed between GDF-15 and each of the MMPs—MMP2, MMP3, MMP9, and TIMP as well as New York Heart Association (NYHA) class and echocardiographic parameters (left ventricular ejection fraction (LVEF) and left ventricular internal dimension in diastole (LVIDd)). LVEF and LVIDd were obtained by two-dimensional echocardiography. The protocol was approved by Scott and White Memorial Hospital Institutional Review Board (S&W IRB). Correlation analysis of control versus all DCM patients showed a strong correlation of GDF-15 with TIMP1 ( r = 0.83, p < 0.0001) and weaker correlation with MMP3 ( r = 0.41, p = 0.011) and MMP2 ( r = 0.47, p = 0.003). MMP9 showed poor correlation with GDF-15 ( r = 0.3036, p = 0.046). GDF-15 correlated negatively with MMP2/TIMP1 ratio ( r = −0.47, p = 0.006). sST2 correlated strongly with GDF-15 ( r = 0.7, p < 0.0001). GDF-15 correlated negatively with LVEF ( r = −0.49, p = 0.004) and positively with LVIDd ( r = 0.58, p = 0.0006). GDF-15 showed significant positive correlation with NYHA functional class ( r = 0.71, p < 0.00001) and BNP ( r = 0.86, p < 0.00001). Significant associations of GDF-15 with MMPs, sST2, LVIDd, LVEF, and NYHA class reported here for the first time in nonischemic dilated hearts may open up new avenues of investigations to better understand molecular mechanisms controlling cardiac remodeling. This study is limited by its small size and needs validation in larger populations.